Scientific Publications Format IMRaD for Social and Humanities Research: A Chance to Be Heard - I. M. Zashikhina; O. V. Pechinkina (Высшее образование в России)
The requirement to submit and publish scientific articles in indexed journals has become a part and parcel of life in academia. Although Russian scientists are becoming more visible in the world of science due to their research achievements, they are not sufficiently recognised by a wide audience for several reasons. In this study, we scrutinize the published papers of Russian researchers working in the domains of social sciences and humanities. We aim at investigating the logic and organisation of such publications to see how the articles correspond to the meta-requirements established by the international academia. To achieve the goal we have analysed the logic and organisation of 55 published articles from the Russian scientometric database e-Library. The results emphasise that most Russian researchers do not follow the IMRaD format accepted by the majority of international journals. As a result, such articles have minimal chances to be accepted by international editors. This is not surprising, as unclear structure means lack of readability and, consequently, loss of readers accustomed to a certain article format. This situation causes concerns because Russian scientists do have a lot to say to the world of science.